Sosialisasi Pentingnya Memahami Karakteristik Dan Tipe-tipe Investasi Ilegal Untuk Meminimalisir Risiko Finansial - Ratna Dumilah; Tanjung, Asridah Warni; Ellesia, Nindie (Jurnal Inovasi Pengabdian Masyarakat, 2025)
The purpose of this community service activity is to provide an understanding of the importance of understanding the characteristics and types of illegal investments to minimize financial risks for mothers who are members of the Family Empowerment and Welfare (PKK) RW 07, Jombang Village. The method used in implementing community service activities is material presentation. The technique used in implementing community service activities is brainstorming and discussion with 25 (twenty five) participants at PKK RW 07 Jalan Sumatera Kampung Rawa Lele RT 004 RW 007, Jombang Village, Ciputat District, South Tangerang City, Banten 15414. The output of this community service activity is a scientific article published through the Community Service Innovation Journal, as well as increasing the growth and development of creativity, scientific attitudes, professional attitudes, caring attitudes and sensitivity to developments and problems faced related to illegal investments and financial risks, in mothers who are members of the Family Empowerment and Welfare (PKK) RW 07, Jombang Village